ATTRIBUTES BASED POSITIONING - Runggu Besmandala Napitupulu; Marion Sibarani; Chainar Elly Ria (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
The study aims at finding out the main attributes in the development of the Darma Agung University and finding the closest competitor of Darma Agung University. The problem of this study is: How is the position of Darma Agung University in competing with other private universities in Medan? Research respondents were 500 people spread over 5 universities. The analysis technique used is descriptive quantitative and multi-dimensional scale correspondenindice analysis. The research findings are: The characteristics of respondents from Darma Agung University are different with the University of Dharmawangsa Medan, but similar to the those from the University of Medan Area, Pembangunan Panca Budi University, and Tjuk Nyak Dhien University; The most desirable attributes by the community from the University are the rating of study program accreditation and the ability of lecturers in teaching; Attributes in five universities are seen as similar, namely: Completeness of books in the library and the convenience of laboratory space; The attributes in the five universities that are considered to have the highest dissimilarity are: Parking area, lecturers’teaching ability, classroom comfort, and openness in governance; Darma Agung University and Pembangunan Panca Budi Medan University are seen similarly by the community (both in quadrant II) on the spatial map; Darma Agung University is viewed by unequal communities (in a different quadrant) on a spatial map with three other universities (Tjut Nyak Dhien University, Medan Area University, and Dharmawangsa University Medan).